(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This study aims to investigation the role of artificial intelligence technique, especially adopting neural networks, in detecting earnings management in Iraqi companies, especially at the local level, which has been exacerbated by the high rates of financial and administrative corruption in Iraq due to fraudulent accounting practices through the use of neural network technology, as there are many studies. Which dealt with neural network technology, including a study entitled (Using artificial neural networks in developing the role of the auditor in discovering fundamental errors), a study at the Higher Institute for Financial and Accounting Studies by researchers (Al-Mamouri and Al-Husseini, 2015). Since profit manipulation involves intentional fraudulent acts, it is necessary to implement preventive measures to detect and deter such practices. The researchers adopted the analytical method as well as the use of neural networks technology through the use of financial ratios. The researchers used the beneish model and neural network technology on a sample of Iraqi companies listed on the Iraqi Stock Exchange, numbering (10) economic units for the years (2017 and 2018). The reason for choosing the years The availability of financial data for the years 2017 and 2018 has shown that the use of the Beneish model led to the emergence of three economic units that practice earnings management. When applying neural network technology, the result of this technology was identical to the beneish model, as there were no errors, and this technology can be used to help auditors discover profit management. The researchers concluded that applying artificial intelligence techniques such as neural networks in auditing helps the auditor detect manipulation of profits through the results reached using neural networks. The use of the Beneish model can effectively determine earnings management and enhance the functions of accounting information systems. This includes improving system speed and efficiency, ensuring accurate output, and enhancing system security. Researchers call for the use and development of artificial intelligence techniques within accounting information systems, as well as the use of the Beneish model. This will make it easier to detect earnings management. This study is important by helping auditors use the Beneish model and neural network technology to discover earnings management.